2018 IEEE International Conference on Environment and Electrical Engineering and 2018 IEEE Industrial and Commercial Power Syst 2018
DOI: 10.1109/eeeic.2018.8494392
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil Erosion and Sediment Load for Red River Basin (Vietnam): Impact of Land Use Change and Reservoirs Operation

Abstract: Erosion and sediment transport have critical implications for aquatic ecology, agriculture, water supply and river navigation. In recent years, with the construction and operation of several reservoirs in Red river basin (China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…It is worth noting that the majority of this cumulative trapping rate comes from the Hoa Binh dam-reservoir, as it has had an overwhelming impact on the sediment load in the river system, as analysed above. This estimate is similar to that of previous researchers who reported that approximately 60% of the suspended sediment load in the Da River has been trapped (sedimentation rate) in the Hoa Binh dam-reservoir (Dang et al, 2010;Le, Ranzi, & Rulli, 2018;Ve et al, 2021;Wei et al, 2021).…”
Section: Sediment Trapped Due To the Dam-reservoir Operationssupporting
confidence: 91%
See 1 more Smart Citation
“…It is worth noting that the majority of this cumulative trapping rate comes from the Hoa Binh dam-reservoir, as it has had an overwhelming impact on the sediment load in the river system, as analysed above. This estimate is similar to that of previous researchers who reported that approximately 60% of the suspended sediment load in the Da River has been trapped (sedimentation rate) in the Hoa Binh dam-reservoir (Dang et al, 2010;Le, Ranzi, & Rulli, 2018;Ve et al, 2021;Wei et al, 2021).…”
Section: Sediment Trapped Due To the Dam-reservoir Operationssupporting
confidence: 91%
“…For example, Le et al (2007) reported that the total sediment load decreased by about 70% (measured at the Son Tay station) since the impoundment of the Hoa Binh. Other studies (Le, Ranzi, & Rulli, 2018; Lu et al, 2015; Ve et al, 2021; Wei et al, 2021) have reported that sediment delivery dramatically decreased from about 50 × 10 6 (1990s) to 12 × 10 6 t/year (2010s), coinciding with the operation of the newest dam‐reservoirs, Tuyen Quang (2008) and Son La (2010). To date, there are nine large dam‐reservoirs (storage capacity >0.1 km 3 ) that have been operated upstream of the Red River system, seven in Vietnam's territory and two in China's territory, namely, Thac Ba (1971), Hoa Binh (1988), Nansha (2008), Tuyen Quang (2008), Madushan (2010), Son La (2010), Ban Chat (2013), Huoi Quang (2015) and Lai Chau (2016).…”
Section: Introductionmentioning
confidence: 95%
“…The land use change that was investigated in this area assumed the conversion of 20% of forest area into rice and agricultural crops and 15% of forest area into bushed, shrubs, and meadows. These cover soil variations showed a 28% increase of sediment load; then, it produced a significant effect on sediment production in the Lo basin [7,8]. Another example of land use impact on water erosion is given by [9], which predicted the variations of runoff and soil erosion in two catchments in Portugal during 2071-2100.…”
Section: Introductionmentioning
confidence: 99%